Invasion genetics of a human commensal rodent: the black rat Rattus rattus in Madagascar. Issue 16 (21st July 2014) - Brouat, C.; Tollenaere, C.; Estoup, A.; Loiseau, A.; Sommer, S.; Soanandrasana, R.; Rahalison, L.; Rajerison, M.; Piry, S.; Goodman, S. M.; Duplantier, J.‐M.
Abstract Studies focusing on geographical genetic patterns of commensal species and on human history complement each other and provide proxies to trace common colonization events. On Madagascar, the unintentional introduction and spread of the commensal species Rattus rattus by people may have left a living clue of human colonization patterns and history. In this study, we addressed this question by characterizing the genetic structure of natural populations of R. rattus using both microsatellites and mitochondrial sequences, on an extensive sampling across the island. Such data sets were analysed by a combination of methods using population genetics, phylogeography and approximate Bayesian computation. Our results indicated two introduction events to Madagascar from the same ancestral source of R. rattus, one in the extreme north of the island and the other further south. The latter was the source of a large spatial expansion, which may have initially started from an original point located on the southern coast. The inferred timing of introduction events—several centuries ago—is temporally congruent with the Arabian trade network in the Indian Ocean, which was flourishing from the middle of the first millennium.